A key genetic factor for fucosyllactose utilization affects infant gut microbiota development - Takahiro Matsuki (Nature Portfolio, 2016)
The factors shaping the development of infants' gut microbiota are poorly understood. Here, the authors show that alterations in gut microbiota development in infants are associated with the presence of bifidobacteria having a gene for utilisation of human milk oligosaccharides.